Factors Affecting Student Online Loan Interest UPN Veteran East Java with Financial Inclusion as Moderator - Johan Oktavian; Tri Kartika Pertiwi (Universitas KH. Abdul Chalim Mojokerto, 2024)
The research begins with the observation that Generation Z tends to be consumptive and lacks finansial knowledge, so they are interested in finding alternative sources of funding such as online loans. There is a significant gap between finansial inclusion in Indonesia and finansial literacy knowledge. This research uses partial least square analysis with SMART PLS 3.0 analysis tool on 392 UPN Veteran East Java students as research objects. The findings of this study indicate that finansial inclusion can act as a moderator between finansial literacy and consumptive behavior on online loan interest. Conversely, finansial literacy has a significant and positive effect on online lending interest, while consumptive behavior has a significant and positive effect on online lending interest. Finansial inclusion cannot act as a moderator between finansial literacy and consumptive behavior on online loan interest.